Analysis Of WPA2 Security Test At PT. Andaglos Global Teknologi Using Fluxion - Dwi Nanda Widiatama; Rionaldi Ali (Proceeding International Conference on Information Technology and Business, 2019)
PT. Andaglos Global Technology uses internet service providers and is equipped with wifi facilities. The location of the office is in the terminal and is adjacent to the shop and other buildings. This resulted in the wifi network at PT. Andaglos Global Technology is often exploited by illegal users around the office, so that the impact on the internet speed decreases. Even the employees of PT. Andaglos Global Teknologi claimed to have been a victim of hacking in its social media after accessing the network at PT. Andaglos Global Technology. To solve this problem, penetration testing is done using FLUXION on PT. Andaglos Global Technology with the method (Action Research) which consists of several stages, namely Diagnosing, Action Planing, Action Taking, Evaluating and Specifyng Learning, to determine the level of security on the network of PT. Andaglos Global Technology. Penetration testing with FLUXION proves that network security at PT. Andaglos Global Technology works well in securing passwords, but FLUXION is able to get passwords from these networks, not by breaking into security but by deceiving network users by creating the same login form as the routers used by PT. Andaglos Global Technology, so that unknowingly network users have given the password to the fake login page, which resulted in the network being accessed by usersillegally.Keywords: Wireless Network Penetration Testing, Fluxion